Hypofractionated Stereotactic Radiotherapy for Non-breast or Prostate Cancer Oligometastases: A Tail of Survival Beyond 10 Years - Aujla, Khush S.; Katz, Alan W.; Singh, Deepinder P.; Okunieff, Paul; Milano, Michael T. (Frontiers in Oncology, 2019)
Purpose and Objective(s): We sought to analyze the long-term follow-up of patients treated with hypofractionated, stereotactic radiotherapy (HSRT) for oligometastases from malignancies other than breast or prostate cancer. Materials and Methods: From 2001 to 2006, 82 cancer patients with 1–5 radiographically apparent metastatic lesions (in 1–3 organs) from primary sites other than breast or prostate cancer, were enrolled on a prospective study of HSRT. Freedom from widespread metastasis (FFWM) was defined from date of enrollment until death, an event (i.e., widespread distant metastasis not amenable to local therapy), or last radiographic study. Local recurrence was scored as an event if pathologically confirmed or if a treated lesion increased by ≥20% using RECIST criteria. Prognostic variables were assessed using Cox regression analysis. Results: The mean age was 61 ± 11 years, with a male to female ratio of 46:36. The most common metastatic sites were liver (50%), lung (48%), thoracic lymph nodes (18%), and bone (5%). Sixty-one patients (74%) had 1 involved organ and 18 (22%) had 1 lesion treated. The preferred dose-fractionation scheduled was 50 Gy in 10 fractions (52 patients). The median follow-up was 1.7 years. Eleven patients lived >5 years, and 6 lived >10 years. The 5-year OS, PFS, FFWM, and LC rates were 13.4, 7.3, 18.3, and 63.4%, and the 10-years OS, PFS, FFWM, and patient LC rates were 7.3, 6.1, 13.4, and 62.2%, respectively. A greater net gross tumor volume (GTV) was significantly adverse for OS (p < 0.01) and LC (p < 0.01). For FFWM, net GTV was not a significant factor (p = 0.14). Four patients remain alive at >13 years from enrollment and treatment, without evidence of active disease. Conclusion: A small subset of select non-breast, non-prostate cancer patients with limited metastasis treated with HSRT are long-term survivors. Net GTV is a significant factor for tumor control and survival. Further research is needed to help better select patients most likely to benefit from local therapy for metastatic disease.